A review on the temperature and moisture degradation of adhesive joints. (August 2017) - Viana, G; Costa, M; Banea, MD; da Silva, LFM
Despite offering very attractive advantages over traditional joining methods, one of the setbacks of adhesive bonding is its long-term strength in aggressive environments, such as environments with high moisture and extreme temperatures. With the rise of new lightweight materials and their recent use in everyday vehicles, transportation industries have been very interested in determining the long-term behavior of adhesive joints. The aim is to build durable, lighter vehicles, which consume less energy and emit less pollution. The two main factors that affect the strength of vehicle adhesive joints are exposure to moist environments and high and low temperatures. There are some works concerning the effect of these two factors separately and some predictive models have been developed, which help the engineer to design reliable, safe, and efficient adhesive joints. However, the combined effect of temperature and moisture is not yet totally understood. This paper presents a review on the temperature and moisture degradation of adhesive joints.